Tópicos Em Ciências Da Saúde 2022
DOI: 10.37423/220605969
|View full text |Cite
|
Sign up to set email alerts
|

Coinfecção Entre Aspergillus Spp. E Sars-Cov-2

Abstract: Resumo: Vários estudos vêm demonstrando que a resposta imunológica exacerbada em infecção pela SARS-COV2, chamada de tempestade de citocinas em pacientes, onde seu estágio de infecção da COVID-19 é avançado. Tendo assim, uma maior dificuldade na escolha de tratamento e elevando o risco desses indivíduos a evoluir para um quadro grave e complexo, dificultando a melhora e escolha terapêutica adequada. Devido a sua variedade fisiopatológica, vários mecanismos homeostáticos estão envolvidos, um deles é a deficiênc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Its multidrug resistant strains are emerging rapidly and gaining the focus of research to find effective antibiotic against this pathogen. Current study observed high prevalence of A. baumannii in age group 41 to 60 and greater than 60 years from tracheal aspirates and sputum respectively, endorsed by other study (12). Present study reported that majority of patients were admitted in HDU and Medical ICU, which is consistent with the studies reported earlier (13).…”
Section: Snosupporting
confidence: 91%
“…Its multidrug resistant strains are emerging rapidly and gaining the focus of research to find effective antibiotic against this pathogen. Current study observed high prevalence of A. baumannii in age group 41 to 60 and greater than 60 years from tracheal aspirates and sputum respectively, endorsed by other study (12). Present study reported that majority of patients were admitted in HDU and Medical ICU, which is consistent with the studies reported earlier (13).…”
Section: Snosupporting
confidence: 91%